The Profile of Elementary Teachers’ Understanding in STEAM (Science, Technology, Engineering, Art, and Mathematics) Approach - Riyanti, Esti Dewi; Roshayati, Fenny; Purnamasari, Veryliana (Jurnal Ilmiah Sekolah Dasar, 2020)
An approach is needed to face the challenges of the 21st century and the 4.0 industrial revolution to improve the quality and quality of education, one of which is by introducing teachers to the STEAM approach. This study analyses the profile of elementary school teachers’ understanding of the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach. This type of research is descriptive qualitative. The subject of this research is teacher understanding. Data collection in this study was carried out by observation, interview, questionnaire, and documentation methods. The instrument used in this study was a non-test instrument in the form of a questionnaire. The data obtained were analyzed using qualitative descriptive statistical analysis techniques using data triangulation. This study’s results obtained that the number of answers from each respondent’s score obtained an average of 55.58. Based on the results of data analysis and discussion, it can be concluded that the principal and teachers do not know about the STEAM (Science, Technology, Engineering, Arts, and, Mathematics) as a new approach that can be used in the learning process that involves student activity. This research aims to develop students’ soft skills,  cooperation, critical thinking, environmental care, responsibility, adaptation skills, and creative thinking.